ANALISIS PENGARUH STORE ATMOSPHERE DAN FOOD QUALITY TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN WARAK KOFFIE PURWOKERTO - Susilowati, Ika (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2018)
Consumer purchasing decisions is important to note because this will certainly be a consideration for the customer to make a purchase. This research aims to analyze the influence of Store Atmosphere and food quality against consumer purchasing decisions. The respondents in this study was consumers Warak Koffie taken as many as 126 people with gender composition of 114 men and women of those 12 people. The results showed that store atmosphere and food quality together gave significant influence towards purchasing decisions.Keywords : Consumer purchasing decisions, Store Atmosphere, Food Quality